Serum procalcitonin to differentiate acute antepartum pyelonephritis from asymptomatic bacteriuria and acute cystitis during pregnancy: A multicenter prospective observational study. Issue 1 (27th October 2021) - Huang, Shang‐Yu; Hsiao, Ching‐Hua; Zhang, Xue‐Qin; Kang, Lin; Yan, Jian‐Ying; Cheng, Po‐Jen
Abstract: Objective: To examine whether serum procalcitonin (PCT) is useful for differentiating acute pyelonephritis (APN) from asymptomatic bacteriuria and acute cystitis during pregnancy. Methods: A multicenter prospective observational study was conducted to compare serum white blood cell (WBC) counts, erythrocyte sedimentation rate (ESR), C‐reactive protein (CRP) level, and PCT level among pregnant women with asymptomatic bacteriuria, acute cystitis, and APN and healthy pregnant women (controls). Utility of WBC count, ESR, CRP, and PCT biomarkers for the prediction of APN during pregnancy were measured. Results: Area under the curve (AUC) values of PCT, CRP, ESR, and WBC count for predicting asymptomatic bacteriuria were 0.576, 0.628, 0.542, and 0.532, respectively; those for predicting acute cystitis were 0.766, 0.735, 0.681, and 0.597, respectively; and those for predicting acute pyelonephritis 0.859, 0.763, 0.711, and 0.732, respectively. Compared with the other inflammatory markers used to predict APN, PCT exhibited the highest AUC (0.859 [95% confidence interval (CI) 0.711–0.935]). A cutoff value of >0.25 ng/ml had a sensitivity of 87% and a specificity of 79%. Conclusion: Serum PCT can be a valuable addition to existing methods of differentiating asymptomatic bacteriuria, acute cystitis, and APN during pregnancy and can facilitate the early identification of APN during pregnancy. Abstract : Serum procalcitonin can be a valuable marker of differentiating asymptomatic bacteriuria, acute cystitis, and acute pyelonephritis during pregnancy.